Effect of reaction time of university table tennis players on different velocities and directions - Chuang, W.-C.; Lin, Y.-F. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
The purpose of this study was to discuss the effect of the reaction time on velocities, ball coming directions to intercollegiate players. The subjects were table tennis school team players from National Kaohsiung University of Hospitality and Tourism, male 13, female 7, total 20 persons in the aggregate of 20 people. Subjects` average age 21.9 ± 2 years, length of playing table tennis 10.1 ±3 year. To investigate the effect of the winging back reaction time from velocities ( independent variable A ) and ball coming direction (independent variable B) to the subjects by taking the imitation of real games serving from real players. Analyse by 2-way ANOVA, the result shows that: 1.Velocities to swing back reaction time had a significant pact. 2. Ball coming direction to receiving reaction time had a significant pact. 3. Velocities and ball coming direction to receiving back reaction time did not exert an influence of interaction. The study concluded: Different velocities and directions were a main effect individual receive and confront faster velocity and ball directions from left result faster reaction time.